PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE WORD SQUARE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 37 PEKANBARU - Mar Febriana; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:This study was conducted because of low yields VA grade social studies student of SD Negeri 37 Pekanbaru. Of the 37 student who achieve KKM a many as people (45,95), while student who do not reach the KKM is 20 people (54,05) with an average of 74,83 .the poruse of this research to improve learning outcomes IPS VA grade student of SD Negeri 37 Pekanbaru learning model application word square. A model word square is a learning model that uses boxs as a tool in a conveying a teacing materials in a the learn a teaching, in a model of word square there questions and a also answer where the answerto every question is inserted into the boxs then student looking for answer on the question by shading in answer given in the box a either vertically,horizontally or diagonally. Analysis of the research data base a score IPS student learning outcoms increasein cycle I and II. This increase is evident from the results of student learning before using model a is 74,83 square on the second cycle increased a 77,16. The percentage of teacher activity after applied learning models a square word at the first meeting of the first cycle that 70,83 square on the second cycle increased a 77,16. The percentage of teacher activity after applied learning models a word square at the first meeting of the first cycle 70,83 increast in the fourth meeting of the scond cycle becomes a 95,83 % with a categori very well. . It can be concluded that the application of cooperative learning model word square can improve learning outcomes IPS graders VA SD Negeri 37 Pekanbaru.Key Word: Word Square,Learning Outcomes IPS.